2020
DOI: 10.1007/s10827-019-00736-2
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations and concentration dynamics of brain tissue oxygen in neonates and adults

Abstract: The brain is a metabolically demanding organ and its health directly depends on brain oxygen dynamics to prevent hypoxia and ischemia. Localized brain tissue oxygen is characterized by a baseline level combined with spontaneous oscillations. These oscillations are attributed to spontaneous changes of vascular tone at the level of arterioles and their frequencies depend on age. Specifically, lower frequencies are more typical for neonates than for adults. We have built a mathematical model which analyses the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…These studies suggest that such oscillations may represent an “on–off” feedback mechanism and provide a pump-like effect leading to improved tissue perfusion via temporary increases in the pressure gradient down the vascular tree. This hypothesis has been further supported by computational simulation, wherein low-frequency CBF oscillations supply higher amplitudes of localized oxygen delivery relative to oscillations at a higher frequency 16 . Furthermore, pulsatile blood flow can increase shear stress on the vessel endothelium which stimulates the release of nitric oxide and inhibits endothelin production, thus increasing oxygen delivery to brain tissue 18 , 21 .…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…These studies suggest that such oscillations may represent an “on–off” feedback mechanism and provide a pump-like effect leading to improved tissue perfusion via temporary increases in the pressure gradient down the vascular tree. This hypothesis has been further supported by computational simulation, wherein low-frequency CBF oscillations supply higher amplitudes of localized oxygen delivery relative to oscillations at a higher frequency 16 . Furthermore, pulsatile blood flow can increase shear stress on the vessel endothelium which stimulates the release of nitric oxide and inhibits endothelin production, thus increasing oxygen delivery to brain tissue 18 , 21 .…”
Section: Introductionmentioning
confidence: 74%
“…Specifically, pulsatile blood flow can increase shear stress on the vessel endothelium which stimulates the release of nitric oxide and inhibits endothelin production, thus increasing oxygen delivery to brain tissue 21 . Furthermore, these oscillatory patterns represent an “on–off” feedback mechanism that serves to maintain tissue perfusion in the setting of oxygen deprivation with computational models suggesting that low frequency oscillatory flow is beneficial to tissue oxygenation 15 , 16 . It might be that brief, rhythmic increases in CBF during the oscillatory stimulus (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, ALFF also can be related to non-neuronal vasomotion. The dominant frequency of brain tissue oxygen oscillations (BTOO), which are attributed to vasomotion at the level of arterioles (Hudetz et al, 1998;Aalkjaer et al, 2011;Mateo et al, 2017), has been shown to change during development (Doubovikov and Aksenov, 2020). The dominant frequency of BTOO is around 1-2 cycles/min (0.0167-0.0333 Hz) in neonates (Aksenov et al, 2018) and approximately 10 cycles/min (0.167 Hz) in adults (Linsenmeier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In adults, it is characterized by a 10 cycles per minute (cpm) dominant power frequency ( 35 , 36 ), whereas underdeveloped vasomotion has a dominant frequency below 3 cpm ( 37 ). This shift in frequency of vasomotion and corresponding brain tissue oxygen oscillations represents a normal development and is needed to prevent localized hypoxia depending on the oxygen demand by developing neurons and neuronal networks ( 36 ). If neonatal anesthesia affects the development of the glutamatergic system, GABAergic system, or normal formation of astrocytes, the development of vasomotion can be affected as well.…”
Section: The Possible Relationship Between Anesthesia-induced Apoptotic Neurodegeneration Neurovascular Interactions and Fmrimentioning
confidence: 99%